The Utilization of Android-Based Application as a Stunting Prevention E-Counseling Program Innovation during Covid-19 Pandemic - Friska, Erlin; Andriani, Helen (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Stunting in children is one of the most significant barriers to human development, globally affecting approximately 162 million children under 5 years of age. During the Covid-19 pandemic, the development of communication and information media such as smartphones has encouraged the creation of various kinds of application-based health innovations known as mobile health. The purpose of this study was to analyze the utilization of android-based applications as a stunting prevention e-counseling program innovation in the Covid-19 pandemic era. Subjects and Method: This research was a systematic review. The articles were selected from Google Scholar, PubMed, ScienceDirect, and Elsevier. The keywords for this review are: prevention, education, stunting counseling, Covid-19, android-based stunting prevention application, stunting counseling application during the Covid-19 pandemic, application for stunting, android application for stunting. The search process to exclude the articles used for this literature review using the PRISMA method. Results: The results showed that the existence of an Android-based stunting prevention application innovation can make it easier for the public to monitor health, obtain the education, and provide counseling to health workers. This is in line with government policies during the Covid-19 pandemic which urges the public to limit activities. Conclusion: The conclusion of this study is android-based applications are very friendly if used by the wider community because they can access information anytime and anywhere, are more flexible, and affordable.